Esophagogastric junction adenocarcinoma shares characteristics with gastric adenocarcinoma: Literature review and retrospective multicenter cohort study. Issue 1 (26th October 2020) - Imamura, Yu; Watanabe, Masayuki; Oki, Eiji; Morita, Masaru; Baba, Hideo
Abstract: The incidence of esophagogastric junction (EGJ) adenocarcinoma has been gradually increasing in Asia, just like in Western countries a few decades ago. Despite recent advances in next‐generation sequencing and multimodal treatments, EGJ adenocarcinoma is still an aggressive malignancy with poor outcomes. Clinically, EGJ adenocarcinoma can be separated into Barrett's adenocarcinoma and cardiac adenocarcinoma, with frequent similarities observed. Barrett's adenocarcinoma is likely to be of gastric origin in terms of its premalignant background, risk factors, and stem cell regulators. Recent comprehensive genomic analyses suggest that immunotherapy may be essential for high‐level microsatellite instability (MSI‐H)‐ and Epstein‐Barr virus (EBV)‐associated subtypes, and against the immunosuppressive phenotype in genomically stable (GS) subtypes, in the treatment of EGJ and gastric adenocarcinoma. Although the chromosomal instability (CIN) subtype dominates EGJ adenocarcinoma, there is still a need to investigate the other molecular subtypes and their targets. Because of the distinctive characteristics of tumor location of EGJ adenocarcinoma, we also described the results of a multicenter cohort study of EGJ adenocarcinoma, comparing Siewert type I (distal esophagus), II (cardia of the stomach), and III (subcardia) tumors. We show that type I tumors were frequently accompanied by Barrett's esophagus (78%, P  < .0001), with a significantly unfavorable outcome (multivariate EGJ‐cancer‐specific mortality hazard ratio = 1.81, 95% CI, 1.06‐2.97; P  = .031). In addition, over half (56%) of these cases experienced disease recurrence in the lymph nodes. Our findings suggest that Barrett's adenocarcinoma may be an aggressive phenotype of EGJ adenocarcinoma due to the potential risk of tumor spread through the complex lympho‐vascular network of the esophagus. Abstract : In this review article, we discussed future therapeutic targets of adenocarcinoma of esophagogastric junction (EGJ) according to the four molecular subtypes by TCGA. We also referred to the current understanding of the similarity between Barrett's adenocarcinoma and cardiac carcinoma, and added our own analysis examining prognostic differences between those two tumors using a multicenter cohort in Japan.